2022
DOI: 10.1108/jd-04-2022-0083
|View full text |Cite
|
Sign up to set email alerts
|

Who are the 100 largest scientific publishers by journal count? A webscraping approach

Abstract: PurposeHow to obtain a list of the 100 largest scientific publishers sorted by journal count? Existing databases are unhelpful as each of them inhere biased omissions and data quality flaws. This paper tries to fill this gap with an alternative approach.Design/methodology/approachThe content coverages of Scopus, Publons, DOAJ and SherpaRomeo were first used to extract a preliminary list of publishers that supposedly possess at least 15 journals. Second, the publishers' websites were scraped to fetch their port… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 44 publications
0
8
0
2
Order By: Relevance
“…We utilized the list in Nishikawa-Pacher’s study, which identified and ranked the top 100 publishers by number of affiliated journals in their portfolio. 23 The largest publisher on the list produced 3763 journals, and the smallest publisher produced 76 journals. In total, these 100 publishers are responsible for the publication of 28 060 journals.…”
Section: Methodsmentioning
confidence: 99%
“…We utilized the list in Nishikawa-Pacher’s study, which identified and ranked the top 100 publishers by number of affiliated journals in their portfolio. 23 The largest publisher on the list produced 3763 journals, and the smallest publisher produced 76 journals. In total, these 100 publishers are responsible for the publication of 28 060 journals.…”
Section: Methodsmentioning
confidence: 99%
“…So, such corporations, companies and publishers would be directly affected by RTBF, and subjected to these laws. We note here that two large OA publishers, MDPI and Frontiers (Nishikawa‐Pacher, 2022), are located in Switzerland, which is not in the European Union. Therefore, GDPR does not apply in Switzerland but does apply to Swiss corporations that operate in EEA countries, as occurs with these two publishers.…”
Section: Crossing the Bridge Between Rtbf And Academia: Do Rtbf Princ...mentioning
confidence: 91%
“…To identify policies to be analysed, existing lists and rankings of academic publishers found online ( Nishikawa-Pacher, 2022 ; Wikipedia, 2023 ) were combined to form a master list of academic publishers which would be investigated. These publishers included traditional scholarly publishers, preprint servers, university publishing houses, general book publishers, newspapers, academic integrity focus groups, and NGOs.…”
Section: Methodsmentioning
confidence: 99%